Distinct effects of positive and negative music on older adults' auditory target identification performances. Issue 11 (November 2014) - Vieillard, Sandrine; Bigand, Emmanuel
Older adults, compared to younger adults, are more likely to attend to pleasant situations and avoid unpleasant ones. Yet, it is unclear whether such a phenomenon may be generalized to musical emotions. In this study, we investigated whether there is an age-related difference in how musical emotions are experienced and how positive and negative music influences attention performances in a target identification task. Thirty-one young and twenty-eight older adults were presented with 40 musical excerpts conveying happiness, peacefulness, sadness, and threat. While listening to music, participants were asked to rate their feelings and monitor each excerpt for the occurrence of an auditory target. Compared to younger adults, older adults reported experiencing weaker emotional activation when listening to threatening music and showed higher level of liking for happy music. Correct reaction times (RTs) for target identification were longer for threatening than for happy music in older adults but not in younger adults. This suggests that older adults benefit from a positive musical context and can regulate emotion elicited by negative music by decreasing attention towards it (and therefore towards the auditory target).